Oral Health in Adults with Diabetes: Oral Health Conditions, Knowledge and Practice Following an Oral Health Educational Program - Marwa S. El-Ashkar; Zahira M. Gad; Mohamed D. El-Borgy; Nevein S. Abdalla; Nessrin A. El-Nimr (Journal of High Institute of Public Health, 2019)
Background: Diabetes mellitus is a risk factor for impaired oral health. Oral health knowledge is lacking among patients with diabetes. Objective(s): The objectives of the study were to assess the oral health condition of patients with controlled and uncontrolled diabetes, to assess knowledge and practice of patients with diabetes concerning oral health and to construct, implement and evaluate the impact of an educational program for patients with diabetes on their oral health, their knowledge and self-reported practice regarding oral health. Methods: A sample of 200 adult patients with diabetes mellitus attending two hospitals in Alexandria was included in the study. In phase 1, a cross sectional design was used and assessment of the patients’ diabetes control, their oral health condition, knowledge and self-reported practice was carried out. In phase 2, an educational oral health intervention program was constructed and its effect on the patients’ oral health condition, knowledge and self-reported practice was done. Results: Most patients with diabetes had unsatisfactory glycemic control, 27.5% had good knowledge, while 75% had poor oral health practice. The oral health condition of patients with satisfactory diabetes control was relatively better than those with unsatisfactory control. The knowledge score, practice, gingivitis, plaque and calculus indices improved after the intervention Conclusion: Better glycemic control is associated with better oral health conditions. Patients with diabetes had insufficient oral health knowledge and poor practice. The educational program improved their knowledge and practice, while some parameters of oral health improved.